A single-center observational study on long-term neurodevelopmental outcomes in children with tuberous sclerosis complex - Mammadova, Dilbar; Vecko, Julia; Hofmann, Marlene; Schüssler, Stephanie; Deiters, Ludger; Canda, A.; Wieland, Anna; Gollwitzer, Stephanie; Hamer, Hajo; Trollmann, Regina (Orphanet Journal of Rare Diseases, 2023)
Background: Tuberous sclerosis complex (TSC) is a rare multisystem disorder caused by mutations in the TSC1 or TSC2 gene. More than 90% of patients with TSC develop neurological and/or neuropsychiatric manifestations. The aim of the present study was to determine the developmental and cognitive long-term outcomes of pediatric TSC patients. Methods: This cross-sectional, monocenter study included pediatric TSC patients who received multidisciplinary long-term care with a last visit between 2005 and 2019. Neurological manifestations and cognitive development (BSID, K-ABC) were analyzed in relation to age and type of mutation. Results: Thirty-five patients aged 13.5 ± 7.8 years were included in the study. Diagnosis was confirmed genetically in 65.7% of patients (TSC1, 26.1%; TSC2, 65.2%; NMI, 8.7%). Mean age at diagnosis was 1.3 ± 3.5 years; 74.3% of the patients had been diagnosed within the first year of life due to seizures (62.9%) or/and cardiac rhabdomyomas (28.6%). The most common TSC manifestations included structural brain lesions (cortical tubers, 91.4%; subependymal nodules, 82.9%), epilepsy (85.7%), and cardiac rhabdomyomas (62.9%). Mean age at seizure onset was 1.5 ± 2.3 years, with onset in 80.0% of patients within the first two years of life. Infantile spasms, which were the first seizure type in 23.3% of the patients, developed earlier (0.6 ± 0.4 years) than focal seizures (1.8 ± 2.5 years). Refractory epilepsy was present in 21 (70.0%) patients, mild or severe intellectual impairment in 66.6%, and autism spectrum disorders in 11.4%. Severe cognitive impairment (33.3%) was significantly associated with epilepsy type and age at seizure onset (p < 0.05). Conclusions: The results emphasized the phenotypic variability of pediatric-onset TSC and the high rate of neurological and neuropsychiatric morbidity. Early-onset refractory epilepsy was associated with impaired cognitive development. Children of all ages with TSC require multidisciplinary long-term care and individual early-intervention programs.
CRIS-Team Scopus Importer:2023-11-17
Keywords: Antiseizure medication; Autism; Cognition; Rare disease; Refractory epilepsy; Tuberous sclerosis complex

Development of the EPO-Score – a multivariable tool to predict adverse outcome in infants with perinatal asphyxia undergoing therapeutic hypothermia – a retrospective study - van der Donk, Adriana; Schleier, Maria; Bär, Alisa; Mulzer, Linda-Marie; Trollmann, Regina; Schüssler, Stephanie; Hebert, Steven; Hanslik, Gregor; Wölfle, Joachim; Reutter, Heiko Martin; Morhart, Patrick (Frontiers in Pediatrics, 2025)
Aim: Early outcome prediction in neonates with perinatal asphyxia receiving therapeutic hypothermia (TH) remains difficult. Although several studies have explored prognostic markers and proposed scoring systems, none of these tools has been adopted for routine bedside use to date. The present retrospective study aimed to design an early prognostic outcome score (EPO-Score). The score serves to identify patients at discharge, predicting severe adverse outcomes according to the Griffiths Mental Development Scales (GMDS) with one year. Methods: Perinatal data was collected from 44 infants with perinatal asphyxia who had received therapeutic hypothermia between 2010 and 2020 at the University Hospital Erlangen, Germany. 27 predictive variables were analyzed regarding their prognostic significance. Analysis showed significant correlations between 15 variables and their outcome. Outcome at one year was classified as favorable (GMDS DQ > 78) or severe adverse (DQ < 78, cerebral palsy, or death). We combined related variables into four indices: systemic injury, neurologic, liver and renal damage. A forward-looking step-by-step analysis revealed a model, explaining 62.1% of the variance in the outcome (R2 = 0.621; p < 0.001). Based on these results, we developed the EPO-Score and correlated the score to the follow-up assessment at one year. Results: A total of 32 (out of 44) infants met the inclusion criteria. 25 infants experienced a favorable outcome, 7 infants a severe adverse outcome. The EPO-Score integrates eight routine predictors. Average EPO-Score among all infants was 11 points (range 0–24). The EPO-Score showed significant association with the developmental outcome at one year of age (R2 = 0.421, p < 0.001). ROC-analysis demonstrated the EPO-Score's ability to distinguish between favorable and severe adverse developmental outcome, with a cut-off value of 13.5 (AUC = 0.926; 95% CI 0.831–1.00). Infants with a score of 14 or higher were classified as high-risk. Conclusion: EPO-Score underlines the correlation between the severity of early multi-organ involvement and severe adverse outcome, demonstrating a high predictive value within our study population. Early identification of patients with severe adverse outcome is important for optimizing neurodevelopmental therapies and providing family support. Nevertheless, external validation is required before the score can be implemented in routine clinical care.
CRIS-Team Scopus Importer:2025-08-29
Keywords: asphyxia; cerebral palsy; Griffiths mental development scales; hypothermia treatment; hypoxic ischemic encephalopathy; neonatal outcome

Hybrid reflected-ultrasound computed tomography versus B-mode-ultrasound for muscle scoring in spinal muscular atrophy - Danko, Vera; Jüngert, Jörg M.; Schüssler, Stephanie; Bühler, Adrian; Klett, Daniel; Federle, Anna; Roos, Andreas; Lochmüller, Hanns; Neurath, Markus; Wölfle, Joachim; Trollmann, Regina; Waldner, Maximilian; et al. (Journal of Neuroimaging, 2023)
Background and Purpose: Novel light- and sound-based technologies like multispectral optoacoustic tomography (MSOT) with co-registered reflected-ultrasound computed tomography (RUCT) could add additional value to conventional ultrasound (US) for disease phenotyping in pediatric spinal muscular atrophy (SMA). The aim of this study was to investigate the quality of RUCT compared to US for qualitative and quantitative assessment of imaging neuromuscular disorders. Methods: Subanalyzing the MSOT SMA study, 288 RUCT and 276 US images from 10 SMA patients (mean age 9.0 ± 3.7) and 10 gender- and age-matched healthy volunteers (HV; mean age 8.7 ± 4.3) were analyzed for quantitative (grayscale levels [GSLs]) and qualitative (echogenicity, distribution pattern, Heckmatt scale, and muscle texture) muscle changes. RUCT and US measures were further correlated with clinical standard motor outcomes. Results: Quantitative agreement using GSLs revealed significantly higher GSLs in muscles of SMA patients compared to healthy muscles in both techniques (US mean GSL [SD] SMA vs. HV: 110.70 [27.8] vs. 68.85 [19.2], p <.0001; RUCT mean GSL [SD] SMA vs. HV: 91.81 [21.8] vs. 59.86 [8.2], p <.0001) with good correlation with motor outcome tests, respectively. Qualitative agreement between methods for muscle composition was excellent for differentiation of pathological versus healthy muscles, echogenicity, and distribution pattern, moderate for Heckmatt scale, and poor for muscle texture. Conclusions: The data suggest that RUCT may allow the assessment of basic qualitative and quantitative measures for muscular diseases with comparable results to conventional US.
CRIS-Team Scopus Importer:2023-01-20
Keywords: neuromuscular disorders; optoacoustics; photoacoustics; spinal muscular atrophy; ultrasound

Long-term outcomes of very-low-birth-weight and low-birth-weight preterm newborns with neonatal seizures: A single-center perspective - Schüssler, Stephanie; Schmidt, Martina; Deiters, Ludger; Candova, A.; Fahlbusch, Fabian; Trollmann, Regina (European Journal of Paediatric Neurology, 2022)
Objective: Newborn seizures are frequent in preterm newborns and indicate brain lesions in many cases. The objective of this observational study was to investigate the long-term outcome of very-low-birth-weight (VLBW) and low-birth-weight (LBW) preterm infants with neonatal seizures. Methods: We examined 54 preterm infants (40 VLBW and 14 LBW cases) born between 2008 and 2011 with clinical seizures during the neonatal period confirmed by interictal or ictal electroencephalography recordings in a retrospective single-center study. Neurodevelopmental follow-up included an expert neurological examination and cognitive testing (Kaufman Assessment Battery for Children) at a mean age of six years. Results: The (mean ± standard deviation) gestational ages of the VLBW and LBW infants were 27.2 ± 1.9 weeks and 33.4 ± 1.7 weeks, respectively, and the postnatal age at seizure onset was 13 ± 11 days in VLBW infants and 9 ± 8 days in LBW infants, with a wide range of one to 62 days. LBW infants more frequently developed non-motor seizures (50.0%) than VLBW infants did (25.0%), and higher-grade intracranial hemorrhage was the predominant etiology in the VLBW group (18.0%), while the etiology in the LBW group was more heterogeneous and included central nervous system malformations and genetic syndromes. At the mean age of 6.2 ± 2.0, years, 25/54 patients were assessed and 44.4% of the VLBW group and 71.4% of the LBW group showed intellectual impairment. Infantile cerebral palsy was present in 22% of VLBW and 42.9% of LBW infants, respectively. Significance: The present analysis of long-term neurodevelopmental outcomes of preterm neonates who experienced seizures shows that the risk for intellectual impairment is not limited only to VLBW infants but may significantly affect LBW infants as well. The etiological spectrum differs in relation to gestational age.
CRIS-Team Scopus Importer:2022-01-14
Keywords: Cognitive development; Neonatal EEG; Neurodevelopmental outcome; Preterm; Prognosis

Multispectral optoacoustic tomography for non-invasive disease phenotyping in pediatric spinal muscular atrophy patients - Regensburger, Adrian; Wagner, Alexandra; Danko, Vera; Jüngert, Jörg M.; Federle, Anna; Klett, Daniel; Schüssler, Stephanie; Buehler, Adrian; Neurath, Markus; Roos, Andreas; Lochmüller, Hanns; Wölfle, Joachim; et al. (Photoacoustics, 2022)
Proximal spinal muscular atrophy (SMA) is a rare progressive, life limiting genetic motor neuron disease. While promising causal therapies are available, meaningful prognostic biomarkers for therapeutic monitoring are missing. We demonstrate handheld Multispectral Optoacoustic Tomography (MSOT) as a novel non-invasive imaging approach to visualize and quantify muscle wasting in pediatric SMA. While MSOT signals were distributed homogeneously in muscles of healthy volunteers (HVs), SMA patients showed moth-eaten optoacoustic signal patterns. Further signal quantification revealed greatest differences between groups at the isosbestic point for hemoglobin (SWL 800 nm). The SWL 800 nm signal intensities further correlated with clinical phenotype tested by standard motor outcome measures. Therefore, handheld MSOT could enable non-invasive assessment of disease burden in SMA patients.
CRIS-Team Scopus Importer:2021-11-26
Keywords: Multispectral optoacoustic tomography; Optoacoustics; Photoacoustics; Spinal muscular atrophie

Seizures in preterm infants with germinal-matrix-intraventricular hemorrhage (GM-IVH): a retrospective monocentric study on predictors and neurodevelopmental outcome - Schüssler, Stephanie; Paul, Anna; Niederreiter, Undine; Deiters, Ludger; Fahlbusch, Fabian B.; Morhart, Patrick; Trollmann, Regina (European Journal of Paediatric Neurology, 2025)
Aim: Germinal-matrix-intraventricular hemorrhage (GM-IVH) is a leading cause of seizures in preterm infants. This study aimed to analyze risk factors associated with seizures and to evaluate neurodevelopmental outcomes in preterm infants with GM-IVH and seizures. Methods: We conducted a retrospective study from 2011 to 2019, identifying preterm infants with GM-IVH grades 2–4 through an electronic patient file system. Seizures were diagnosed based on clinical manifestations and abnormal EEG findings. Infants were grouped by the presence or absence of seizures, and associated comorbidities were compared. Neurodevelopmental follow-up was assessed at two years of age using the Mental Bayley Scales of Infant Development II (BSID-II). Outcomes of infants with seizures were compared to all tested preterm infants with birth weight <1500 g born between 2011 and 2019 (n = 195). Results: A total of 34 preterm infants with GM-IVH grades 2–4 were included. Seizures occurred in 52.9 % of cases. Their occurrence was significantly associated with lower gestational age (mean 28.1 vs. 30 weeks, p = 0.04) and pneumonia (p = 0.003). Infants with seizures had significantly lower BSID-II Mental scores (n = 15) compared to those without seizures (86.3 ± 18.3 vs. 104.9 ± 8.5, p = 0.03). However, as these infants had a lower gestational age, we could not distinguish if they had a poorer outcome because of seizures or because of immaturity. Conclusion: Seizures in preterm infants with GM-IVH were significantly associated with lower gestational age and pneumonia. Infections and inflammation may contribute to seizure development. Larger studies with continuous EEG monitoring are needed to validate these findings.
CRIS-Team Scopus Importer:2025-05-09
Keywords: Bayley scales; Electroencephalography; Neonatal brain injury; Neurodevelopmental follow-up; Pneumonia